Annotation and curation of uncharacterized proteins- challenges - Ijaq, Johny; Chandrasekharan, Mohanalatha; Poddar, Rajdeep; Bethi, Neeraja; Sundararajan, Vijayaraghava S. (Frontiers in Genetics, 2015)
Hypothetical Proteins are the proteins that are predicted to be expressed from an open reading frame (ORF), constituting a substantial fraction of proteomes in both prokaryotes and eukaryotes. Genome projects have led to the identification of many therapeutic targets, the putative function of the protein and their interactions. In this review we have enlisted various methods. Annotation linked to structural and functional prediction of hypothetical proteins assist in the discovery of new structures and functions serving as markers and pharmacological targets for drug designing, discovery and screening. Mass spectrometry is an analytical technique for validating protein characterisation. Matrix-assisted laser desorption ionization–mass spectrometry (MALDI-MS) is an efficient analytical method. Microarrays and Protein expression profiles help understanding the biological systems through a systems-wide study of proteins and their interactions with other proteins and non-proteinaceous molecules to control complex processes in cells and tissues and even whole organism. Next generation sequencing technology accelerates multiple areas of genomics research.